How employee stock options and executive equity ownership affect long-term IPO operating performance - Pukthuanthong, Kuntara; Roll, Richard; Walker, Thomas (Journal of Corporate Finance, 2007)
To ascertain whether the form of managerial compensation affects a firm's long-term operating performance, we track IPOs for 5 years after the expiration of the stabilization period. New public companies perform better when managers receive a balanced combination of stock option grants and equity ownership. Firms with unbalanced compensation arrangements, large option grants and little equity ownership or vice versa do not perform as well. This empirical finding is consistent with a theoretical explanation based on managerial risk aversion and the alignment of managerial and owner incentives.